2012
DOI: 10.1002/hep.25930
|View full text |Cite
|
Sign up to set email alerts
|

Liver vitamin D receptor, CYP2R1, and CYP27A1 expression: relationship with liver histology and vitamin D3 levels in patients with nonalcoholic steatohepatitis or hepatitis C virus

Abstract: Evidence suggests an association between low serum 25-hydroxy-vitamin D 3 [25(OH)D 3 ] levels and the presence and prognosis of liver disease. Vitamin D receptor (VDR) has been widely detected in the liver, but its expression in the course of liver disease has never been investigated. We evaluated the hepatic expression of VDR along with that of vitamin D 25-hydroxylases in patients with nonalcoholic steatohepatitis (NASH) or chronic hepatitis C (CHC) and its relationship with hepatic histological features an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
155
4
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(169 citation statements)
references
References 38 publications
9
155
4
1
Order By: Relevance
“…This extrarenal production of 1,25(OH) 2 VD, together with a wide VDR availability, allows a local paracrine/autocrine regulation. In fact, 1,25(OH) 2 VD controls the expression of many genes, playing a key role in cell proliferation, differentiation, inflammation, and immunity (24,25).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This extrarenal production of 1,25(OH) 2 VD, together with a wide VDR availability, allows a local paracrine/autocrine regulation. In fact, 1,25(OH) 2 VD controls the expression of many genes, playing a key role in cell proliferation, differentiation, inflammation, and immunity (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…In the liver, VDR is expressed in cholangiocytes, and this expression has been shown to be inversely associated with steatosis severity, lobular inflammation, and NAFLD score in adult patients with NASH (25). Moreover, both animal and human data suggest that 1,25(OH) 2 VD may have anti-fibrogenic effects (25,26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, vitamin D deficiency has been correlated with a more severe NAFLD activity score and hepatic fibrosis [78] , perhaps owing to the greater oxidative stress resulting from vitamin D deficiency [79] . Hepatic expression of vitamin D receptors, CYP2R1 and CYP 27A1, negatively correlates with the severity of steatosis, inflammation, and NAFLD scores in patients with this disease [80] . A recent study found a significant association between NAFLD and low serum vitamin D levels [81] ; this relationship remained significant even after adjustments were made for the presence of other metabolic syndrome features.…”
Section: Vitamin Dmentioning
confidence: 94%
“…AMPK, 5' adenosine monophosphate-activated protein kinase; Ask-1, apoptosis signal-regulating kinase 1 (Ask-1 is also known as mitogen-activated protein kinase kinase kinase 5 (MAP3K5)); CCL2 chemokine (C-C motif) ligand 2 (CCL2 is also referred to as monocyte chemoattractant protein 1 (MCP1)); CCR, chemokine receptor; FGF-21, fibroblast growth factor-21; JNK, C-Jun-Nterminal kinase; mTOR, mechanistic target of rapamycin/ mammalian target of rapamycin; PPARs, peroxisome activated proliferated receptors α, γ and δ; NF-kB, nuclear factor-kB; Nrf 2, nuclear factor (erythroid-derived 2)-like 2; FXR, farnesoid X receptor; SREBPs, sterol regulatory element binding protein. Hepatic inflammation and fibrosis 79,80 .…”
Section: Glossary Termsmentioning
confidence: 99%